Changes in the balance of body fluids during extensive endurance training session - Jürimäe, J.; Jürimäe, T.; Purge, P. (2001)
The purpose of this investigation was to study the influence of extensive endurance rowing training session on body fluids in 12 experienced rowers (23.3± 6.3 yrs; 188.7± 5.9 cm; 82.0± 10.8 kg; BMI: 23.7± 2.1 kg.m-2). All rowers had a light traditional breakfast about three hours before the training session. The subjects rowed on single sculls 2 hr 17 min and covered 22.6± 2.5 km. Before, immediately after the training session, and after 30, 60 and 120 min of recovery, body fluid balance was measured using multiple-frequency bioelectrical impedance device (Multiscan-5000, Bodystat Ltd, UK). Body resistance was measured on the right side of the body. Extracellular- (ECW), intracellular- (ICW) and total (TBW) body water were measured at 5, 200 and 50 kHz, respectively. Blood hemoglobin (Hgb) and hemotocrit (Hct) were measured, and changes in the blood volume (BV), plasma volume (PV) and cellular volume (CV) were estimated according to Dill and Costill (1974). Body weight of rowers decreased significantly (p<0.01) from 82.0± 10.8 to 80.6± 11.2 kg during the endurance training. There were no significant changes in TBW immediately after the training session. Significant changes in the content of TBW occurred during the first 30 min of recovery (48.9± 4.4 to 47.9± 4.1 l; p<0.05). The amount of ECW also decreased significantly during the first 30 min of recovery (23.3± 2.0 to 22.7± 1.9 l; p<0.05). There were no significant changes in the balance of ICW as a result of endurance training session. BV decreased during the training session by 2.5± 5.2% (p>0.05). There were significant relationships (p<0.05) between the covered distance and the following variables after the training session: body weight (r= -0.75), TBW (r= -0.75) and ECW (r= -0.83). Changes in the blood parameters did not correlate significantly with changes in body fluids and training volume. It was concluded that extensive rowing training session significantly changed the balance of body fluids in rowers.